ASSESSMENT OF CHANGES IN SEASONAL DYNAMICS OF WATER QUALITY OF THE SYRDARYA RIVER IN WINTER - Malokhat A. Mirzakarimova; Islam A. Usmanov; Amangul Zh. Kurbanbaeva; Larisa G. Tetyukhina (Central Asian Journal of Medicine, 2024)
The article presents information on the water quality of the Syrdarya river in the winter of 2023 according to organoleptic and chemical indicators. The analyses of the selected water samples were carried out in accordance with the water quality standard for water supply sources UzSSt 951. It was found that, according to organoleptic and chemical indicators, the water quality of the Syrdarya river in the studied areas of water use by the population meets the imposed hygienic requirements. However, the indicators of total hardness and mineralization (based on dry residue) of the Syrdarya river water in the initial sections exceed the established hygienic standards.